Implementasi Prepopulated Pajak Masukan Dan SPT Masa PPN Pada Aplikasi Efaktur 3.0 - Rd Kusyeni; Ryan Nugraha; Sudarwanto Sudarwanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The Directorate General of Taxes (DGT) has released the effector application version 3.0, and its implementation is carried out in stages, namely: the first stage is implemented on 1 February 2020 limited to only 4 LTO Tax Service Offices and the Intermediate Tax Service Office, the second stage in June 2020 is implemented to 27 Taxable Entrepreneurs (PKP) at the LTO Tax Service Office and the Intermediate Tax Service Office in Jakarta, the third phase in August at the LTO Tax Service Office and Representative Tax Service Offices in Madya. On 1 October 2020 this version 3.0 effector was implemented nationally. There are several significant changes from the previous ones including: Prepopulated Input Tax, Import Declaration (PIB) and Tax Return (SPT). Prepopulated Input Tax is not a new application, but an additional application from the 3.0 version of E-faktur, this prepopulated technology is useful for reducing manual work that has been done so far inputting Input Tax data and Goods Import Declaration (PIB) data, so as to reduce input errors that have often occurred. Through prepopulated Taxes for Entrepreneurs, Taxable Entrepreneurs (PKP) do not need to input manually and do not need a QR code scanner application because the input tax effectors data on NPWP and PKP is available by the system and the crediting period is available to be selected according to the crediting provisions. For prepopulated PIB, the benefits that are owned are: Taxable Entrepreneurs (PKP) do not need a key in and there is no more error inputting the State Revenue Transaction Number (NTPN) PIB data on the NPWP of Taxable Entrepreneurs (PKP) which is available by the Directorate General of Taxes system ( DJP) and the Directorate General of Tax and Excise (DJPC). Because the Directorate General of Taxes has been connected with the Directorate General of Tax and Excise on a house to house basis. For VAT period reporting, it will be easier with prepopulated reporting through a web-base affectivity of all tax output data and documents uploaded are available when reporting the VAT period e-spt. It is hoped that this feature will help taxpayers in an effort to report SPT correctly, completely and clearly.